2016
DOI: 10.1007/s10792-016-0411-4
|View full text |Cite
|
Sign up to set email alerts
|

Refractive outcome of combined phacoemulsification and endoscopic cyclophotocoagulation

Abstract: Refractive outcome after phaco-ECP is comparable to phacoemulsification alone. This study suggests that the intraocular lens power can be selected for cataract surgery alone and that ECP does not change the effective lens position significantly; therefore, no modification of biometry formulae is required. Phaco-ECP should be considered as an effective, safe and predictable surgical treatment option for glaucoma patients with co-existing cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 11 publications
(12 reference statements)
2
17
0
Order By: Relevance
“…Keratometry measurements also play a significant role in IOL calculations [15]. Because MIGS surgeries use the pre-existing clear corneal wound used for phacoemulsification, they should not add any induced astigmatism beyond what is already induced by the cataract extraction itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Keratometry measurements also play a significant role in IOL calculations [15]. Because MIGS surgeries use the pre-existing clear corneal wound used for phacoemulsification, they should not add any induced astigmatism beyond what is already induced by the cataract extraction itself.…”
Section: Discussionmentioning
confidence: 99%
“…The effect on post-operative refraction has previously been evaluated in other MIGS procedures with mixed results. Kang et al found no change in refractive outcome between phacoemulsification alone compared to phacoemulsification plus ECP [15]. Conversely, Sheybani et al demonstrated that ECP performed in addition to phacoemulsification led to an increase in the rate of myopic surprise compared to cataract surgery alone [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSL and ECP aim to provide a safer, less invasive means of lowering IOP than traditional filtering surgeries and are associated with significantly fewer complications. [5789101118] In patients with mild-to-moderate glaucoma and surgically naive eyes, Siegel et al demonstrated the following postoperative complication rates of phaco/ECP in 261 eyes: CME in 1.5%, retinal detachment in 0.7%, and transient IOP elevations in 8%, without any cases of hyphema, persistent inflammation, or hypotony. [19] The patients in our study did not experience any surgical complications.…”
Section: Discussionmentioning
confidence: 99%
“…The technique of combining phacoemulsification with ECP (phaco/ECP) has emerged as a viable option to simultaneously treat both cataract and glaucoma. [710]…”
mentioning
confidence: 99%